The relationship between affective polarization and democratic backsliding: comparative evidence. Issue 4 (19th May 2022) - Orhan, Yunus Emre
ABSTRACT: Why do voters vote for undemocratic politicians in a democracy? My chief contention is that affective polarization has become a primary factor driving support for undemocratic politicians. Once partisan identification turns into a salient identity in the hierarchy of group affiliations, it has the potential to widen inter-party distances. Such a political environment fosters positive beliefs of their preferred party and negative beliefs of the other party, which promote political cynicism, intolerance and increase partisan loyalty. As a result, crossing party lines becomes costly, even when incumbents violate democratic principles or incumbents' economic policies do not appeal to supporters' interests. This tradeoff enables undemocratic politicians to evade electoral sanctions for undemocratic behaviour. I created an extended version of Reiljan's affective polarization application. The new dataset covers affective polarization scores of 53 countries calculated over 170 national election surveys. I find that increasing affective polarization is highly correlated with democratic backsliding, less accountability, less freedom, fewer rights, and less deliberation in democracies. However, ideological polarization has shown no correlation.